Unlocking Oral Proficiency Through the Shadowing Technique Combined with VOA: The Experimental Impact on Undergraduate Speaking Abilities - Siti Ayu Surayya; Ari Prasetyaningrum; Usuludin Usuludin; Ahmad Khatami (UIBU, 2024)
Speaking is a skill that presents substantial challenges for students and incorporates a variety of different aspects. This study examined the influence of the Shadowing technique, which employed Voice of America (VOA) special English as a modern media in teaching and learning process. A comparison was conducted between two groups of undergraduate students in their fourth semester: an experimental group that received instruction using the Shadowing technique through VOA media and a control group that received no training. The research was considered to be quasi-experimental. Twenty students majoring in English were included in the study's sample. An analysis of the results of the pre-test and post-test scores was performed using a non-parametric test, namely the Man-Whitney U form. The results of this analysis revealed that the experimental group had significantly improved their speaking abilities. The implementation of the Shadowing technique can be a highly supportive method for improving students' pronunciation skills when used with VOA Learning English as a modern media, providing educators with valuable material to enhance language proficiency. Consequently, adopting this approach could lead to significant advancements in the teaching and learning of speaking skills. However, doing further study in diverse settings and over prolonged durations is necessary to have a more profound understanding of the efficacy and durability of the approach.